Canine status epilepticus due to acute intoxication - Zimmermann, R.; Steinberg, T. A.; Raith, K.; Hülsmeyer, V.; Fischer, A. (Tierärztliche Praxis Ausgabe K: Kleintiere / Heimtiere, 2010)
Objectives: The purpose of this study was to describe the type of toxin ingested, clinical presentation and outcome of dogs with status epilepticus (SE) due to acute poisoning presented to a large referral veterinary hospital. Materials and methods: Retrospective case series. Medical records of all dogs suffering from SE were reviewed (Jan 1, 2002 to April 30, 2009). Results: Fourteen dogs with SE due to acute intoxication were identified. Toxicological analyses (qualitative analysis with gas chromatography/mass spectrometry; n = 11) detected poisonings with carbofuran, crimidine, paraoxone, metaldehyde, strychnine and diazinon. In the other three cases the uptake of a known poison was observed (zink phosphide, metaldehyde). None of the dogs showed evidence of neurological disease up to the day of presentation. The dogs were hospitalised for 2–10 days (median 5 days). The survival rate was 85.7%. None of the dogs experienced any more seizures after discharge (median observation period 2.6 years). Conclusion and clinical relevance: Ancillary to the acute clinical presentation, preliminary reports (possible uptake of poisonous material) and an inconspicuous medical history may suggest a tentative diagnosis. Managed adequately, these patients can have a high survival rate. Clinicians should also keep uncommon intoxications in mind.
Keywords: Poisoning; case series; dog; epilepsy; organophosphates; carbamates; metaldehyde; crimidine; strychnine; zinc phosphide